INNOVATIVE TEACHING STRATEGIES TO BOOST STUDENT ACHIEVEMENT - Ary Purwantiningsih (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2023)
In an era of rapid educational transformation, traditional teaching methods are increasingly being replaced by innovative approaches aimed at improving student engagement and achievement. This study explores the implementation of innovative teaching strategies—such as project-based learning, flipped classrooms, gamification, and the use of educational technology—and their impact on student learning outcomes. Using a qualitative descriptive method, data were collected through interviews and classroom observations involving secondary school teachers who actively apply such strategies. The results reveal that these approaches foster active learning, critical thinking, and increased motivation, leading to improved academic performance. However, the study also highlights key challenges, including limited resources, lack of training, and institutional resistance. The findings suggest that while innovative teaching holds great potential, its success depends on systemic support, teacher readiness, and a shift toward learner-centered education. This research contributes to the growing discourse on effective pedagogical reform and underscores the need for sustainable innovation in education.